2007
DOI: 10.1097/01.ta.0000240452.64138.b0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Calcium-Based Demineralized Bone Matrix/Allograft for Nonunions and Posttraumatic Reconstruction of the Appendicular Skeleton: Preliminary Results and Complications

Abstract: The use of Allomatrix/demineralized bone matrix as an alternative for autogenous bone graft in the treatment of nonunions resulted in an unacceptably high rate of complications. Although we recommend further study, we do not recommend the use of Allomatrix for the treatment of nonunions, especially if there is a large volumetric defect or a history of any prior contamination of the tissue bed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 7 publications
0
52
0
Order By: Relevance
“…14,16,17,32 Complications encountered have included persistent drainage from the wound, superficial or deep infection, and failure of union. No reports of allergic reaction, metabolic derangement, or end organ damage have been reported.…”
Section: Complicationsmentioning
confidence: 99%
“…14,16,17,32 Complications encountered have included persistent drainage from the wound, superficial or deep infection, and failure of union. No reports of allergic reaction, metabolic derangement, or end organ damage have been reported.…”
Section: Complicationsmentioning
confidence: 99%
“…Ziran et al reported that use of CS in non-unions led to no improvement in bone healing and increased wound drainage because of its rapid resorption within 6-8 weeks. 35 Therefore, CS is not recommended for non-unions or periarticular fractures, but Osteoset bone graft substitutes may be used as a drug carrier to deposit tobramycin in local areas. According to the aforementioned studies, CP is difficult to resorb within one year in clinical use, and HAp lasts longer than CP.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, it has been well established that DBM is capable of stimulating new bone formation, but also that its combination with osteoprogenitor cells produces better results [16,109,110]. In humans this approach proved controversial as the use of injectable demineralised bone resulted in a high rate of complications [123]. Percutaneous bone grafting on the other hand has been proven successful in the safe treatment of nonunions [5,54,56].…”
Section: Discussionmentioning
confidence: 99%
“…Their results revealed an 85.1% union rate. On the other hand, a recent study by Ziran et al, which evaluated an open application of a new calcium sulphate-demineralised bone matrix/allomatrix in the treatment of nonunions, presented an unacceptably high rate of complications which included postoperative drainage (54%), deep infection (34%) and an overall failure rate of 46% [123].…”
Section: Percutaneous Pattymentioning
confidence: 99%